PEREMPUAN ABORIGIN DAN TALANG MAMAK: SEBUAH ANALISIS KOMPARATIF - Aris, Qori Islami (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
This study explores women's roles in Aboriginal and Talang Mamak societies within their respective social and domestic contexts. It involves a comparative analysis of two literary texts, 'Alinta, The Flame' by Hyllus Maris and Sonia Borg, and 'Behuma' by Gunawan, representing the Aboriginal and Talang Mamak cultures, respectively. The primary focus of this research is to compare and analyze women's roles in these indigenous cultures while considering the social, cultural, and economic factors that influence their positions in both the public and domestic spheres. Additionally, it assesses the contributions of these literary works to our comprehension of the roles of women from Aboriginal and Talang Mamak cultures, particularly within the framework of their distinctions between public and domestic roles. This study adopts a descriptive-analytical approach, intending to provide a comprehensive account of the existing phenomena. In this context, it delineates the comparative roles of Aboriginal and Talang Mamak women as portrayed in 'Alinta, The Flame' and 'Behuma.' The findings suggest that Aboriginal society exhibits a greater degree of patriarchy than Talang Mamak society, as evidenced by the lower participation of Aboriginal women in the public sphere.